Allogeneic Hematopoietic Cell Transplantation for Dyskeratosis Congenita: A Report of 3 Cases. Issue 7 (October 2017) - Tamura, Shinichi; Imamura, Toshihiko; Urata, Takayo; Kobayashi, Miki; Gen, Mari; Tomii, Toshihiro; Do, Junko; Osone, Shinya; Ishida, Hiroyuki; Hosoi, Hajime; Kuroda, Hiroshi
Abstract : Although bone marrow failure in patients with dyskeratosis congenita (DKC) can be successfully treated with allogeneic hematopoietic cell transplantation (allo-HCT) using a reduced intensity conditioning (RIC) regimen, the outcome of nonhematological disorders in patients with DKC treated with allo-HCT using RIC has not been fully elucidated. Here, we describe the clinical course of nonhematological disorders after allo-HCT with RIC in 3 consecutive patients with DKC. Allo-HCT with RIC was feasible in all cases; however, patient 1 developed lethal pulmonary disease and patient 2 experienced progression of hepatic fibrosis. Careful follow-up of patient-specific complications is required after allo-HCT in patients with DKC.